The Effect of Ge Content on the Optical and Electrical Properties of A-Sige: H Thin Films - Mursal Mursal; Irhamni Irhamni; T Winata (Jurnal Natural, 2014)
The effect of Ge content on the optical and electrical properties of a-SiGe:H thin films deposited by HWC-PECVD had been investigated. The a-SiGe:H films ware grown on corning glass 7059 substrate using 10% diluted mixture of GeH4 and SiH4 gases, respectively. The GeH4 gas flow rate was varied from 2.5 – 12.5 sccm, while the flow rate of SiH4 was kept constant at 70 sccm. The results showed that the deposition rate of a-SiGe:H thin films increased by  increasing of GeH4 gas flow rate. In addition, the Ge content in the film increased and  the optical band gap decreased. The dark conductivity of a-SiGe:H films were relatively constant, whereas the photo conductivity decreased with increasing of Ge content.